A teia narrativa de Inês Pedrosa: narração, tempo e espaço em Fazes-me falta - Trein, Fernanda (2010)
This dissertation aims at analyzing the novel Fazes-me falta, by Inês Pedrosa, in terms of its narrative composition, which is configured by discursive sequences of two characters who are also the narrators (one of them being dead and the other, alive), who engage in a presumed dialogue. Furthermore, our purpose is to analyze time and space in the narrative construction, two elements which stand out from the text, since the female voice is dead and occupies a temporal spot and an existential limbo, whereas the male voice suffers the absence resulting from the disappearance of his friend. Time works as a thread in the narrative, and along with space, it provides the appropriate ambiance for the dialogue between life and death of the two characters, thus supporting the narrative composed by the discourses of these two voices.